Women s' perception on role of breast self-examination in early breast cancer detection - Uzma Kausar; Amir Ahmad; Muhammad Sohail Anjum Noor; Areeba Sohail (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: A good knowledge of the predictive and precepting factors can reduce the risk of breast cancer. This study aimed to assess female patients' knowledge of breast cancer, self-examination techniques, and other screening methods.METHODOLOGY: A cross-sectional descriptive study was carried out at the territory care hospital Khurrianwala Faisalabad, including 500 women attending the outpatient department from June 2022 to November 2022 after taking informed consent. Data collected by filling out a validated questionnaire was analyzed through SPSS software version 22.0. Relationships between categorical variables were tested by using the chi-square test, and a p<0.05 is considered highly significant.RESULTS: Out of 500 study participants, 304(60.8 %) know about breast cancer, of which 64(12.8 %) have a positive family history, 436(87.2 %) have no history of breast cancer, and 196(39.2%) were unaware of breast cancer. Out of the total participants, 60.8 % were aware of Breast self-examination, while 39.2% did not know. There is a significant association for the practice of breast self-examination in the population above higher education p-value≤0.001. Similarly, occupation p-value≤0.001, marital status p-value=0.040, and education p-value≤0.001 have significant associations with BSE.CONCLUSION: The current study showed that knowledge of breast cancer and the practice of BSE and mammography were very poor. A health education program involving the local and governing bodies should be organized to reduce the prevalence and create awareness.